Dakwah Berbasis Teknologi: Integrasi Media Sosial dan AI dalam Perspektif Sosiologi Dakwah - Syukur, Abdul; Aridan, Muhammad; Santoso, Amin Nugrah (WISE Pendidikan Indonesia, 2025)
This study aims to explore the transformative role of social media and artificial intelligence (AI) in contemporary Islamic preaching through a comprehensive literature review. Ten peer-reviewed articles published between 2019 and 2025 were purposively selected to examine the intersection between digital technology and the sociological dynamics of da’wah. The findings reveal that social media has redefined the public sphere of da’wah by fostering participatory, interactive, and community-driven communication models. Concurrently, AI facilitates the automation and personalization of religious content delivery, enhancing accessibility while raising ethical and epistemological concerns. The integration of these technologies has not only revolutionized the methods of da’wah but also disrupted traditional structures of religious authority and knowledge production. The novelty of this study lies in its dual focus on both social media and AI within the sociological framework of da’wah an area that remains underexplored in prior research. The study recommends the development of digital literacy, ethical guidelines for AI-assisted preaching, and a renewed conceptual paradigm for understanding da’wah within a digitized religious ecosystem.